Femoroacetabular impingement in professional ice hockey players. A case series of 5 athletes after open surgical decompression of the hip - Bizzini, M.; Notzli, H. P.; Maffiuletti, N. A. (The American Journal of Sports Medicine, 2007)
Femoroacetabular impingement of the hip joint has been identified as a major cause for hip pain in athletes. Surgical open decompression of the hip has historically been proposed as the first treatment of choice. Functional outcomes in athletes after this procedure are unknown.